The Importance of Water Transport in High Conductivity and High-Power Alkaline Fuel Cells - Mandal, Mrinmay; Huang, Garrett; Hassan, Noor Ul; Peng, Xiong; Gu, Taoli; Brooks-Starks, Ahmon H.; Bahar, Bamdad; Mustain, William E.; Kohl, Paul A. (Journal of the Electrochemical Society, 2019)
High ionic conductivity membranes can be used to minimize ohmic losses in electrochemical devices such as fuel cells, flow batteries, and electrolyzers. Very high hydroxide conductivity was achieved through the synthesis of a norbornene-based tetrablock copolymer with an ion-exchange capacity of 3.88 meq/g. The membranes were cast with a thin polymer reinforcement layer and lightly cross-linked with N,N,N′,N′-tetramethyl-1,6-hexanediamine. The norbornene polymer had a hydroxide conductivity of 212 mS/cm at 80°C. Light cross-linking helped to control the water uptake and provide mechanical stability while balancing the bound (i.e. waters of hydration) vs. free water in the films. The films showed excellent chemical stability with <1.5% conductivity loss after soaking in 1 M NaOH for 1000 h at 80°C. The aged films were analyzed by FT-IR before and after aging to confirm their chemical stability. A H2/O2 alkaline polymer electrolyte fuel cell was fabricated and was able to achieve a peak power density of 3.5 W/cm2 with a maximum current density of 9.7 A/cm2 at 0.15 V at 80°C. The exceptionally high current and power densities were achieved by balancing and optimizing water removal and transport from the hydrogen negative electrode to the oxygen positive electrode. High water transport and thinness are critical aspects of the membrane in extending the power and current density of the cells to new record values.